PEMANFAATAN LIMBAH PEMBAKARAN BATUBARA (BOTTOM ASH) PADA PLTU SURALAYA SEBAGAI MEDIA TANAM DALAM UPAYA MENGURANGI PENCEMARAN LINGKUNGAN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
This research on the utilization of coal-ash that is wasted at the coal-fired power plant is conducted with the intention to become an effort to alleviate environmental impact of the power plant. The by-production of such waste in coal-fired power plants is a direct consequence of the rising demand on electricity as one of human basic needs in modern lifestyle. Endeavor to save the environment is a manifestation of the good culture of environmental awareness; indeed, human being shall act responsibly for the soundness of the environment. Some sufficient amounts in different composition of coal bottom-ash from a coal-fired power plant mixed with another medium were implemented toward a variety of plants, i.e. a certain type of Orchid (“Moon” Orchid or Phalaenopsis amabilis), Tomato (Solanum lycopersicum) , and Sansevieria. A series of mixed medium with different composition (each particular composition is in triplicate), is prepared consisting of 0%, 25%, 50%. 75%, and 100% of Bottom Ash, consecutively. The observed result shows that Bottom Ash is not suitable for the orchid plant as its medium. This more probably results from the fact that the pH of Bottom Ash tends to be more alkaline, while the Orchid plant would only be growing optimally in acidic - normal condition. In the case of Tomato plant, Bottom Ash is usable to be the plant growing medium; in fact an increase of Bottom Ash percentage expedites the plant growth from its seed to become small plants. Another plant under observation is Sansivieria. Bottom Ash turns out to be suitable as a medium for this plant. In fact, this type of plant remains growing steadily and normally in media with variable percentage of Bottom Ash, all along the research procedure. Bottom Ash contains some nutrient that are beneficial to plants, such as Boron (B), Phosphorus (P) and among other elements are Cu, Zn, Mn, Mo dan Se. Most of coal-ashes tend to be alkaline with pH ranging from 8 to12.